Factors related to rapid weight loss practices among international-style wrestlers - Alderman, B. L.; Landers, D. M.; Carlson, J.; Scott, J. R. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The deaths of three intercollegiate wrestlers in 1997 prompted the NCAA and governing bodies that oversee high school sports to adopt new policies prohibiting unsafe weight loss practices. Similar policies have not yet been adopted for international style wrestling, a style that attracts thousands of youth once the regulated scholastic season is over. Therefore, this study examined the rapid weight loss practices in high school wrestlers participating in international style wrestling. To do this, rapid weight gain (RWG), an index that reflects the degree of rapid weight loss (RWL), was examined. METHODS: Wrestlers (N = 2638) participating in the 1997 and 1998 National wrestling championships were randomly selected to be weighed at matside with electronic scales. The methods wrestlers used to accomplish weight loss were also assessed in a subsample of wrestlers. RESULTS: Wrestlers gained an average of 3.4 kg, which represents a 4.81% gain of body weight. The range across weight classes and age groups was -2.68 kg (-2.1% loss of body weight) to +16.73 kg (13.4% gain of body weight). No differences in RWG existed as a function of the represented state teams. In addition, wrestlers who were older and more successful (i.e., placers) gained significantly more weight that their younger and less successful counterparts (P < 0.001). Excessive running, using saunas, and wearing vapor-impermeable suits were cited as the most common methods used to achieve RWL. CONCLUSION: These results suggest that RWL still exists in international style wrestling, and similar policies to those recently instituted by the NCAA are warranted.